(untitled) (Proceedings of International Conference on BioScience and Biotechnology, 2017)
Polymers based on Lactic acid are of great importance to the healthcare industry because they decompose by hydrolysis in the human body in to nontoxic metabolites. Therefore, the objective of the current study was to produce L-(+)-Lactic acid using a low cost medium in order to synthesize a biodegradable polymer for healthcare industry. Powdered cassava was acid hydrolyzed using different concentration of HCl (0.5, 1, 1.5, 2, 2.5, 3, 5, 8 and 10 %) followed by a thermal treatment at 120OC for 10 minutes. Five different media (A- E) were prepared from the above hydrolyzed product along with yeast extract. Lactobacillus casei was inoculated to media A (Cassava- 5 g, Yeast extract-1.5 g, K2HPO4-0.41 g, KH2PO4-0.56 g), B (Cassava- 5 g, Yeast extract 1.5g, MgSO4.7H2SO4- 1 g, (NH4)2SO4-1 g), C (Cassava- 5 g, Yeast extract- 5g, K2HPO4- 2 g, NaAc- 5 g, MgSO4.7H2SO4- 0.02 g, MnSO4.4H2O-0.05 g), D (Cassava- 5 g, Yeast extract- 1.0g, K2HPO4- 0.41g, MgSO4.7H2SO4- 1g, (NH4)2SO4-1g), and E (Cassava crumble- 5 g, Yeast extract- 1.0g, K2HPO4- 0.41g, MgSO4.7H2SO4- 1g, (NH4)2SO4-1g). Medium A, B, and C were inoculated with L. delbrueckii. The lactic acid produced by each species in different media were quantified using Agilent 1260 infinity HPLC. According the Benedict test the 2 % HCl was obtained to provide efficient amount of L-(+)-lactic acid via acid hydrolysis. Medium D fermented with L. casei was identified as the effective low cost medium for large scale fermentation. The lactic acid concentration of the medium D was detected as 259 mg/L. Medium D was identified as effective medium for large scale fermentation for the production lactic acid with L. casei. Purification and polymerization need to be performed in order to synthesis the biopolymer.